Praziquantel coverage in schools and communities targeted for the elimination of urogenital schistosomiasis in Zanzibar: a cross-sectional survey. Issue 1 (December 2016) - Knopp, Stefanie; Person, Bobbie; Ame, Shaali; Ali, Said; Muhsin, Juma; Juma, Saleh; Khamis, Iddi; Rabone, Muriel; Blair, Lynsey; Fenwick, Alan; Mohammed, Khalfan; Rollinson, David
Abstract Background Biannual mass drug administration (MDA) with praziquantel and additional interventions to eliminate urogenital schistosomiasis has been implemented on the Zanzibar islands, United Republic of Tanzania, since 2012. We aimed to assess the coverage of school-based treatment (SBT) and community-wide treatment (CWT), to validate the coverage reported by the Zanzibar Ministry of Health (MoH) and to identify reasons for non-compliance. Methods We conducted a post-MDA cross-sectional survey in 93 schools and 92 communities on Pemba and Unguja islands in early 2014, 3–5 months after the last MDA round. Pupils and adults were asked whether they had received and taken the praziquantel treatment provided in the last SBT or CWT, respectively, and the observed and reported coverage were compared. Reasons for non-compliance were recorded in a pretested questionnaire and assessed in qualitative interviews. Urine samples of participants were examined for Schistosoma haematobium eggs with a single urine filtration. Results Around 8000 pupils and 4000 adults were included in the analysis. Our survey revealed a SBT coverage of 85.2 % in Pemba and of 86.9 % in Unguja, which was in line with MoH reports from Pemba (84.3 %) and higher than reports from Unguja (63.9 %). However, 15 among the 48 schools surveyed in Unguja had not received SBT. Among the interviewed adults, 53.6 % in Pemba and 64.9 % in Unguja had received praziquantel during CWT, which was less than the 59.0 % and 67.7 %, respectively, indicated by MoH reports. Moreover, only 43.8 % and 54.0 % of adults in Pemba and Unguja, respectively, had taken all the tablets as recommended. The main reasons for not receiving or taking praziquantel were absence during CWT, no drug distributor coming, being busy, fear of adverse events, pregnancy, breastfeeding or feeling healthy. Conclusion To increase coverage and compliance in Zanzibar, SBT should target all schools and mobilization, sensitization and implementation of the CWT need to be improved. To reach elimination of urogenital schistosomiasis transmission in Zanzibar and elsewhere, a very high treatment coverage and compliance at national and local level is key and additional control measures such as snail control and behaviour change interventions will need to be implemented area wide. Trial Registration ISRCTN48837681 .